Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1681/asn.2016060664
|View full text |Cite
|
Sign up to set email alerts
|

Is Dietary Red Meat Kidney Toxic?

Abstract: See related article, "mTOR Regulates Endocytosis and Nutrient Transport in Proximal Tubular Cells," on pages 230-241.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…High-protein diets that are rich in red meat accelerate the progression of both experimental and human CKD (12,13). The link between a high-protein diet and CKD ( Figure 2) suggests that one might obtain mechanistic insights from studying mammals that live almost exclusively on a high-protein diet, such as the Felidae family (felids) and Desmodontinae (vampire bats).…”
Section: [H1] High-protein Diets and Dehydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…High-protein diets that are rich in red meat accelerate the progression of both experimental and human CKD (12,13). The link between a high-protein diet and CKD ( Figure 2) suggests that one might obtain mechanistic insights from studying mammals that live almost exclusively on a high-protein diet, such as the Felidae family (felids) and Desmodontinae (vampire bats).…”
Section: [H1] High-protein Diets and Dehydrationmentioning
confidence: 99%
“…High-protein diets induce vasodilation of afferent renal arterioles, glomerular hypertension and hyperfiltration, which together accelerate the progression of pre-existing CKD in a variety of domestic and laboratory animals, including mice, rats and dogs (28). A high consumption of salt and animal proteins has also been linked to progression of CKD in humans (12,29), with increasing evidence indicating a greater effect of red meat consumption compared with that of other animal and vegetable protein sources (12,13).…”
Section: [H1] High-protein Diets and Dehydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In an associated editorial, Wesson and Goraya speculated that the cause of this may be increased metabolic acidosis associated with red meat. (18) One last point that must be kept in mind when evaluating this data was that the majority of the studies were done in a pre-renin-angiotensin system (RAS) blockade era. Now we have those drugs, as well as flozins and mineralocorticoid antagonists which are not just effective, but much less complicated to implement.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…As a strategy to reduce dietary phosphorus intake, several randomized trials have found that replacing foods high in phosphate additives with additive-free foods resulted in significant reductions in serum phosphate concentrations [84] without impacting nutritional status [85]. Approaches aimed at examining associations between diet and ESRD have begun to shift the focus from assessment of individual nutrients to diet patterns and type or quality of foods consumed [86]. As current evidence for traditional dietary restrictions has come into question, liberalization of the renal diet has been suggested [87].…”
Section: Phosphorus and Phosphorus-to-protein Ratiomentioning
confidence: 99%